Differential diagnosis of prosopalgia of dental patients - R. A. Mikhailik; T. A. Lopushanskaya; A. V. Tsimbalistov; N. A. Ogrina (Эндодонтия Today)
Aim. To estimate the size of the areas of the skull holes along the course of the trigeminal nerve in dental patients with prosopalgia according to computed tomography. Materials and methods. Twenty seven dental patients were examined. Clinical methods of examination, palpation, assessment of the intensity pain manifestations using a visual analog scale of pain, clinical index Helkimo. Instrumental methods: gnathodynamometry, spiral computed tomography. Results. The article describes data on the condition of bone canals and skull holes of dental patients with facial pain. 27 dental patients with complaints of pain in the facial area were examined using a visual analog scale of pain, the clinical Helkimo index and spiral computed tomography. The method of measuring the bone channels and holes of the skull is described. Criteria for assessing the degree of asymmetry of bone structures are proposed. Conclusions. The factors of predisposition to prosopalgia of dental patients in the presence of narrowing and pronounced asymmetry of the size of the bone canals of the skull were revealed.